2016
DOI: 10.1016/j.neuroimage.2015.10.077
|View full text |Cite
|
Sign up to set email alerts
|

The Reference Ability Neural Network Study: Life-time stability of reference-ability neural networks derived from task maps of young adults

Abstract: Analyses of large test batteries administered to individuals ranging from young to old have consistently yielded a set of latent variables representing reference abilities (RAs) that capture the majority of the variance in age-related cognitive change: Episodic Memory, Fluid Reasoning, Perceptual Processing Speed, and Vocabulary. In a previous paper (Stern et al., 2014), we introduced the Reference Ability Neural Network Study, which administers 12 cognitive neuroimaging tasks (3 for each RA) to healthy adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 21 publications
3
50
1
Order By: Relevance
“…Positive loadings to this pattern were found within regions associated with the dorsal attention system, and negative loadings were within areas that were reminiscent of the default mode system. 12 In a different study, Stern et al used the same RANN data and determined the number of principal components that optimally predicted premorbid IQ in a linear regression. 11 Regression weights from this analysis were used to create an IQ-related task-invariant BOLD pattern, and expression of this pattern modulated between cortical thickness and fluid reasoning performance among healthy individuals across the age span.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive loadings to this pattern were found within regions associated with the dorsal attention system, and negative loadings were within areas that were reminiscent of the default mode system. 12 In a different study, Stern et al used the same RANN data and determined the number of principal components that optimally predicted premorbid IQ in a linear regression. 11 Regression weights from this analysis were used to create an IQ-related task-invariant BOLD pattern, and expression of this pattern modulated between cortical thickness and fluid reasoning performance among healthy individuals across the age span.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the comparison of BOLD activation patterns from multiple cognitive tasks, several studies identified common regions of activity across conditions. 1214 Recruitment of these regions showed direct associations with CR factors, such as education 12 and premorbid IQ. 13,14 In addition, resting state fMRI, which has the advantage of providing information about the brain’s functional organization rather than regional activity, has also been used in the context of CR.…”
Section: Introductionmentioning
confidence: 99%
“…The data set consisted of participants from two studies: The reference ability neural network (RANN), and the cognitive reserve (CR) studies. The RANN study was designed to identify networks of brain activity uniquely associated with performance across adulthood of each of the four reference abilities: memory, reasoning, speed of processing, and vocabulary (Habeck et al, ). The CR study was designed to elucidate the neural underpinnings of CR and the concept of brain reserve (Stern, ).…”
Section: Methodsmentioning
confidence: 99%
“…Both RANN and CR have been approved by the Institutional Review Board of Columbia University. More detailed information about the two studies can be found in previous publications (Habeck et al, ; Habeck et al, ; Razlighi, Habeck, Barulli, & Stern, ; Stern, ; Stern, ; Stern et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The use of a young, healthy sample mimics the principle of normative modeling in which normative metrics are defined in a cohort of interest (e.g., young and healthy) to investigate deviations due to pathological conditions (e.g., aging and ischemic injury) [26, 27]. The sample of young adults was a subset of a larger sample enrolled in an ongoing imaging study called the Reference Ability Neural Network study (RANN [28, 29]). The inclusion criteria included native English speaking, strongly right-handed, and at least a fourth grade reading level.…”
Section: Methodsmentioning
confidence: 99%